The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)
fs-ref-orig: Société Santé en français. (2019). Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients. fs-code-orig: Société Santé en français-2019